China matters : getting it right for Australia - Gill, Bates (Schwartz Publishing Pty. Ltd, 2017)
A--Australia's prosperity and security are linked to China as never before. But what kind of a country is China becoming? Will its demand for Australian goods and services increase? Can the Communist Party continue to keep the middle class satisfied while cracking down on political freedoms? How will China use its economic and military might, especially if challenged by President Trump?------Rising Star Linda Jakobson is an award-winning, internationally recognised author of six books on China. A Mandarin speaker, she worked as a researcher and policy adviser in China for 22 years before moving to Sydney in 2011 to become East Asia Program Director at the Lowy Institute. In 2015 she founded China Matters, an Australian public policy initiative. A Finnish national she is a permanent resident of Australia.